2. Analisis Pola Kerjasama Aktor Negara dan Non-negara dalam Penanganan Kejahatan Transnasional di Area Konservasi Harimau Sumatera - Birendra, Muhammad Basyir; Windiani, Reni; Rosyidin, Mohamad (Journal of International Relations, 2017)
Sumatran Tiger is endemic sub-species from Indonesia whose status is internationally protected by CITES (Convention on International Trade in Endangered of Wild Flora and Fauna). In 2007, the number of Sumatran Tiger was only around 400 individuals spreads over Sumatran Tiger conservation. In order to respond the thread of extinction of Sumatran Tiger, Indonesian government has established cooperation with International Non Governmental Organization working on wildlife conservation. This research aims to analyze cooperation pattern between Ministry of Environment and Forestry/MOEF with WCS-IP in tackling poaching and illegal trafficking of Sumatran Tiger body parts. This research use the concept of state-nonstate actor cooperation through supplementary pattern, complementary pattern, and adversaries pattern. The result showed that supplementary pattern is done by providing support in human resource and financial sector by WCS-IP, complementary pattern is done by distribution of authority from MoEF to WCS-IP, and adversaries pattern is done by WCS-IP’s support to changes in government policies and regulations. Based from all of the pattern, supplementary pattern is the most dominant because the compatibility between implementations with the concept and fulfill the vision and mission factor, coordination factor, and trust factor.